Perlindungan Sosial Melalui Program Keluarga Harapan di Kelurahan Wagom Distrik Pariwari Kabupaten Fakfak - Kristopel Philipus Uswanas; Ridla Nuraida (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
The Family Hope Program (PKH) is social protection by providing conditional social assistance that must be met first for underprivileged families designated as beneficiaries of the Family Hope Program. The family program was first started in 2007 and implemented by the Indonesian government as a conditional cash transfer. This study aims to determine social protection through PKH in the Wagom Village, Pariwari District, and Fakfak Regency, the problems that occur, and the efforts made by the government to overcome problems that exist in the field. This study uses a qualitative descriptive approach and data collection techniques using interviews, observation, and documentation. Social protection through PKH in the Wagom Village, Pariwari District, Fakfak Regency is one of the government's efforts to reduce poverty. This program assists selected PKH participants, such as low-income families with family members of pregnant/postpartum women, children (SD, SMP, SMA), and the elderly and disabled, with terms and conditions that the beneficiaries must meet. The results of this study reveal that social protection through PKH in the Wagom Subdistrict has been going well, as seen from the process of initial meeting activities, socialization of companions, disbursement of aid, updating of data, and verification of participant commitments. As well as the problems encountered during the implementation of PKH in the field, these problems were based on education and health facilities, as well as problems in the data collection process. Efforts made are increasing socialization, improving services, and improving data.